Osteopetrosis Presenting with Neonatal Thrombocytopenia: A Case Report - Mohammad Kazemian; Minoo Fallahi; Seyed Hossein Fakhraee; Samin Alavi; Naeeme Taslimi Taleghani; Sara Sani (Mashhad University of Medical Sciences, 2018)
Background: Osteopetrosisis an inherited and rare bone disease, characterized by the impairment ofbone modeling and remodeling and the failure of osteoclasts to resorb bone. It also results in skeletal fragility despite increased bone mass, and may cause hematopoietic insufficiency, disturbed tooth eruption, nerve entrapment syndromes, and growth impairment. The infantile form of the disease is the most severe one with a poor prognosis. If untreated, it will result in death by the first decade of life. Case report: A term 10-day-old female neonate with a birth weight of 2850 grams  delivered by caesarian section was reported without a history of parents' consanguinity from a healthy, gravida 2, para 1, abort 1 mother with no complication during pregnancy. The newborn admitted to the neonatal ward due to diffuse petechiae, purpura on the skin, and periorbital ecchymosis (raccoon eyes), without any other abnormal significant signs and symptoms. In laboratory findings except for frequent low platelet count as low as 10000-25000, there wasn't any other abnormalities. Other coagulative tests were within normal ranges. In addition to antibiotics for probable sepsis, platelet transfusion was considered as the treatment, and due to the lack of proper response to the treatment, with suspicious of alloimmune thrombocytopenia, two courses of IV IgG were administered. Eventually, the persistent thrombocytopenia in spite of mentioned treatment led to further investigation , and finally osteopetrosis was diagnosed by the result of brain CTS. The patient was discharged from the hospital with a moderate thrombocytopenia while she needed frequent platelet transfusion. Eventually with bone marrow transplantation, the sign and symptoms of the disease subsided.  Conclusion: In persistent and unjustifiable neonatal thrombocytopenia, diagnosis of osteopetrosis should be considered.